(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Non-Hodgkin lymphoma with concurrent pregnancy produces management dilemma regarding obstetrical aspect and chemoradiation for the disease itself. Successful pregnancy outcome depends upon several factors. Stage of Non-Hodgkin Lymphoma at presentation, gestational age at the time of diagnosis, response to chemotherapy, presence of compression symptoms or systemic B symptoms, concomitant obstetric complications emerging during antenatal follow-up, teratogenic /developmental defects of the unborn baby and its sequel, cardiotoxicity of Doxorubicin in particular are among the various factors affecting management and prognosis of each case. This case report delineates the management of a patient diagnosed as Non- Hodgkin’s lymphoma at 18 weeks of gestation with a successful foetal outcome and ultimate demise of the patient from progressive disease eight months after delivery. DOI: 10.3329/bjog.v24i1.6324 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) :27-31